Tradisi Tumpengan Perspektif Masyarakat Kristen Dan Islam Di Kelurahan Bancarkembar Kecamatan Purwokerto Utara Kabupaten Banyumas - Ida Asyifa; Pangestika Rizki Utami (Jurnal Penelitian Agama, 2021)
Abstract The cone tradition has become a tradition that has been passed down in Bancarkembar Village, Purwokerto Utara. Tumpengan is always served on certain events such as celebrating birthdays, thanksgiving, or events that are formal and informal. The problem is that as a society that has a diversity of religions, it certainly raises a variety of perspectives on giving cone of events held by people of different religions. Will the community in Bancarkembar Village foster an attitude of tolerance or even an attitude of intolerance towards the tradition of the tumpengan. The study used an interview method with one of the residents ofÂ  Bancarkembar Village, Purwokerto Utara. The reason is that the cone is from culture. To analyze cultural problems it is necessary to involve various perspectives, especially from the Muslim and Christian communities. The purpose of the study was to examine whether Bancarkembar village was still tolerant or not with the traditional cone-shaped media. The results of the interview Bancarkembar Village community highly upholds a sense of tolerance towards other religions, especially for the tradition of tumpengan, they are of the opinion that tumpengan is only a tradition and does not need to be extended with religious appendages.